Gene Expression Response to Stony Coral Tissue Loss Disease Transmission in M. cavernosa and O. faveolata From Florida - Traylor-Knowles, Nikki; Connelly, Michael T.; Young, Benjamin D.; Eaton, Katherine; Muller, Erinn M.; Paul, Valerie J.; Ushijima, Blake; DeMerlis, Allyson; Drown, Melissa K.; Goncalves, Ashley; Kron, Nicholas; Snyder, Grace A.; et al. (Frontiers in Marine Science, 2021)
Since 2014, corals within Florida's Coral Reef have been dying at an unprecedented rate due to stony coral tissue loss disease (SCTLD). Here we describe the transcriptomic outcomes of three different SCTLD transmission experiments performed at the Smithsonian Marine Station and Mote Marine Laboratory between 2019 and 2020 on the corals Orbicella faveolata and Montastraea cavernosa. Overall, diseased O. faveolata had 2194 differentially expressed genes (DEGs) compared with healthy colonies, whereas diseased M. cavernosa had 582 DEGs compared with healthy colonies. Many significant DEGs were implicated in immunity, extracellular matrix rearrangement, and apoptosis. These included, but not limited to, peroxidases, collagens, Bax-like, fibrinogen-like, protein tyrosine kinase, and transforming growth factor beta. A gene module was identified that was significantly correlated to disease transmission. This module possessed many apoptosis and immune genes with high module membership indicating that a complex apoptosis and immune response is occurring in corals during SCTLD transmission. Overall, we found that O. faveolata and M. cavernosa exhibit an immune, apoptosis, and tissue rearrangement response to SCTLD. We propose that future studies should focus on examining early time points of infection, before the presence of lesions, to understand the activating mechanisms involved in SCTLD.